Deleuze and Guattari's "Becoming-Child" in Zacada Circus. Issue 7 (17th November 2018) - Fancy, David
Abstract : This transdisciplinary engagement with the figure of the child uses performance studies and philosophy to explore the ways in which youth-involved and youth-oriented circus-theater productions can enable the manifestation of what Deleuze and Guattari describe as "becoming-child."